1996
DOI: 10.1007/bf00731464
|View full text |Cite
|
Sign up to set email alerts
|

Determination of anti-AGE antibodies in human serum

Abstract: The aim of this study was to develop an immunoenzyme method for the determination of anti-AGE antibodies in human serum. Human aortic elastin glycated in vitro (AGE-elastin) was used as an antigen, expressing AGE-epitopes, common to all glycated proteins. Polyclonal serum from guinea-pig against AGE-Hemocyanin was obtained according to Nakayama et al. [(1989) Biochem Biophys Res Commun 162: 740-45] and its specificity was tested via direct and competitive ELISA. Sera of 20 type 1 diabetic patients and 20 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
1
20
0
1
Order By: Relevance
“…As a consequence, new AGE epitopes are formed in and between the chains. In our previous investigation [38] , anti-AGE autoantibodies, common for glycated proteins, were studied. Our future aims are to investigate and compare the antigenic characteristics of glycated and unmodified fibrillins.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, new AGE epitopes are formed in and between the chains. In our previous investigation [38] , anti-AGE autoantibodies, common for glycated proteins, were studied. Our future aims are to investigate and compare the antigenic characteristics of glycated and unmodified fibrillins.…”
Section: Discussionmentioning
confidence: 99%
“…In order to elicit an immune response, a molecule must be recognized as non-self by the biological system. Proteins containing AGE are highly immunogenic and anti-AGE antibodies have been found in the sera of patients with diabetes (Reddy et al, 1995;Shibayama et al, 1999;Baydanoff et al, 1996). Several AGE structures have been identified including pyrraline, pentosidine (Sell & Monnier 1989), (carboxymethyl)lysine (Ahmed et al, 1986), and crosslines (Nakamura et al, 1992).…”
Section: Autoantibodies In Diabetes Complicationsmentioning
confidence: 99%
“…These increased serum levels of AGE can predict changes in microvascular morphology in patients with diabetic retinopathy. Proteins containing AGE are highly immunogenic (Reddy et al, 1995) and anti-AGE antibodies were found in the sera of patients with diabetes (Shibayama et al, 1999;Baydanoff et al, 1996). Our research team has hypothesized that increase in the titre of anti-AGE antibodies has a direct role in the pathogenesis of diabetes microvascular complications especially diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…These antibodies recognize and react with AGE-epitopes regardless of the proteins they have been formed on. Assessment of the levels of these antibodies shows that they are present at low titres even in sera of healthy subjects, perhaps as a part of homeostatic mechanism which clears glycated structures via in situ destruction or via opsonization of the gflycated proteins and products of their degradation (Baydanoff et al, 1996). However, in the conditions of increased nonenzymatic glycation the homeostatic control is inefficient and the generation of these antibodies increases (Baydanoff et al, 1996).…”
Section: Introductionmentioning
confidence: 99%